Influence of iodine application during radioiodine therapy in case of impending therapy failure - Urbannek, V.; Schmidt, M.; Moka, D.; Hillger, H. W.; Voth, E.; Wellner, U.; Schicha, H. (Nuklearmedizin - NuclearMedicine, 2000)
Aim: We investigated whether additional application of “cold” iodine after therapy with radioiodine could result in a prolongation of the effective half life of iodine-131 and would thus lead to an increase of the effective thyroid radiation dose. Methods: Time-activitycurves after therapy with radioiodine were analysed in 25 patients (16 women, 9 men). Nine patients suffered from autonomously functioning thyroid nodules, 5 from autonomous multinodular goiter and 11 from Graves’ disease. These patients had an effective half life shorter than 4 days resulting in an undertreatment of > 20% with respect to the desired effective thyroid radiation dose. 2-4 days after therapy with radioiodine all patients received “cold” iodine for three days in a dose of 3 × 200 μg per day. Results: In 14 of the 25 patients an increase of the effective half life was observed. Patients with an autonomously functioning thyroid nodule showed a mean increase of the effective thyroid radiation dose of 40 ± 44 Gy, patients with toxic multinodular goiter of 29 ± 30 Gy and patients with Graves’ disease of 37 ± 37 Gy. Conclusion: Additional application of “cold” iodine after therapy with radioiodine can prolong the effective half life in selected patients. We suspect a correlation with the thyroid iodine pool. This will be the basis for further investigations hopefully resulting in a better patient preselection to determine who might respond to this therapy.
Keywords: Radioiodine therapy; intrathyreoidal iodine pool; effective half-life for I-131; uptake of I-131; iodine metabolism model